REPRESENTASI IDENTITAS SOSIAL DALAM KONTEN DAKWAH RISALAH AMAR TENTANG PALESTINA: KAJIAN SOSIOLINGUISTIK - Zulfan; Fadillah, Nur; Nasution, Fatimatuzzahra (El-Tsaqafah : Jurnal Jurusan PBA, 2025)
This study aims to analyze the representation of social identity in the digital da'wah content of the Risalah Amar account, which focuses on humanitarian issues in Palestine. This study uses a sociolinguistic approach, incorporating Hymes' (1974) theory of the SPEAKING model, Halliday's (1978) theory of language functions, and Hall's (1997) theory of social representation. The method employed is descriptive qualitative, using observation, note-taking, and documentation techniques for data in the form of videos, captions, and audience comments on Instagram. The results show that the language in Risalah Amar's da'wah content functions as a means of constructing a social identity that represents religious values, humanitarian solidarity, and global awareness. The choice of religious terms such as "syuhada" and "Ashabul Kahfi" serves to reinforce spiritual and ideological meanings. Furthermore, audience interaction in the comments section reflects the emotional involvement and collective solidarity of Muslims with the Palestinian issue. Thus, digital da'wah serves not only as a medium for disseminating religious values ??but also as an arena for constructing social identity and transnational solidarity through linguistic and symbolic practices in the digital space.